L’INFLUENCE DE L’ART POPULAIRE SUR L’ART SAVANT: RÉFÉRENCES ESTHÉTIQUES AUX CRÉATIONS ROUMAINES DANS LA PREMIÈRE MOITIÉ DU XXᵉ SIÈCLE - Liliana-Isabela APOSTU HAIDER (Studia Universitatis Babeş-Bolyai. Musica)
The Influence of the Folk Art on the Savant Art: Aesthetic References to the Romanian Creations in the First Half of the XXth Century. The present study aims at contributing to the development of the knowledge of the compositions of George Enescu and Béla Bartók, stemming from a direct contact of their creators, (formed at the school of the learned musical tradition), with the popular music. Besides, this work proposes a new approach of the interaction between both domains seemingly set, by referring to the violonistique interpretation. The popular musicians of Rumania influenced the thought of both composers, who likened not only popular elements of the language and the directory, but also techniques of instrumental play. It was thus necessary to study the ethno musicological aspects strictly connected to the Rumanian popular tradition, and the anthropological aspects, aiming at the relation of the art with the human society, which produces it. This research joins in the field of the human sciences, because, the art, learned or popular, is produced by the man and addresses the society.